START Triage Video Education Improves Earthquake Disaster Response Knowledge among Anesthesiology Nursing Students: A One-Group Pretest–Posttest Study - Muhammad Zaidan Yudzkar; Anita Setyowati; Raden Sugeng Riyadi (Genius Publishing (CV. Gerbang Ilmu Nusantara), 2026)
Background: Earthquake disasters may cause mass casualties and require rapid victim prioritization through appropriate triage. START triage is a simple method for disaster response, but students’ knowledge of its application may still be limited. Video education may help improve students’ understanding of triage procedures. Objectives: This study aimed to examine the effect of START triage video education on earthquake disaster response knowledge among anesthesiology nursing students. Methods: Quantitative pre-experimental study used a one-group pretest–posttest design. A total of 70 first-semester anesthesiology nursing students were selected using simple random sampling. Participants received a five-minute START triage educational video. Knowledge was measured before and after the intervention using a 20-item questionnaire. Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. Results: Before the intervention, 34.4% of students had good knowledge. After the intervention, the proportion increased to 67.2%. The Wilcoxon test showed a significant improvement in knowledge after video education (p < 0.001). Conclusions: START triage video education significantly improved earthquake disaster response knowledge among anesthesiology nursing students and may be used as a practical learning medium in disaster preparedness education.